Tumour endothelial markers - Kopczyńska, Ewa (Contemporary Oncology/Współczesna Onkologia, 2008)
Tumour growth in great measure depends on development of blood vessels during angiogenesis or postnatal vasculogenesis. Endothelial cells and their precursors play a significant role in both processes. These cells are identified based on specific cell surface markers. For endothelial cells VEGFR-2 is the most characteristic marker. Recently, new markers were identified, i.e. tumour endothelial markers (TEMs). There are nine TEMs (TEM 1-9), but only four of them (TEM1, 5, 7, 8), associated with the cell surface, are of special interest from the biological and clinical point of view. These transmembrane receptors interact with extracellular matrix components. Increased expression of TEMs is observed in the endothelium of various tumour types, especially in colon cancer. Probably TEMs participate in tumour angiogenesis, and they can be an anti-cancer therapy target, particularly TEM8 – the most specific for neoangiogenesis.